2006
DOI: 10.1534/genetics.106.060251
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance Patterns of Transcript Levels in F1 Hybrid Mice

Abstract: Genetic analysis of transcriptional regulation is a rapidly emerging field of investigation that promises to shed light on the regulatory networks that control gene expression. Although a number of such studies have been carried out, the nature and extent of the heritability of gene expression traits have not been well established. We describe the inheritance of transcript levels in liver tissue in the first filial (F 1 ) generation of mice obtained from reciprocal crosses between the common inbred strains A/J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
37
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 45 publications
8
37
0
Order By: Relevance
“…The authors found that the F 1 hybrids exhibited additive expression levels much more frequently than nonadditive levels. The few observations of hybrid gene expression outside of the parental range were typically identified in genes with little expression difference between the inbred parents (Cui et al 2006), similar to the results obtained by Swanson-Wagner et al (2006) in maize.…”
Section: Text Box 2 Describing the Gene Expression Levels In Inbredssupporting
confidence: 75%
“…The authors found that the F 1 hybrids exhibited additive expression levels much more frequently than nonadditive levels. The few observations of hybrid gene expression outside of the parental range were typically identified in genes with little expression difference between the inbred parents (Cui et al 2006), similar to the results obtained by Swanson-Wagner et al (2006) in maize.…”
Section: Text Box 2 Describing the Gene Expression Levels In Inbredssupporting
confidence: 75%
“…Among F1 generations from two inbred mice strains, approximately twothirds of all loci have measurable h 2 with a quarter having an h 2 of >50% (Cui et al, 2006). In both humans and mice, the median h 2 is 34% among loci with measurable h 2 (Cui et al, 2006). The variation in regulatory processes affecting gene expression has been inferred by combining microarray and QTL studies [expressed QTLs (eQTL)].…”
Section: Genetics Of Gene Expressionmentioning
confidence: 99%
“…It has also been hypothesized that the crossing of inbred lines characterized by distinct gene expression levels could lead to advantageous transgressive phenotypic (Birchler et al 2003;Cui et al 2006;Stupar and Springer 2006;Swanson-Wagner et al 2006;Stupar et al 2008). One approach used to study the genetics of phenotypic traits is to measure transcript expression in the hybrids relative to their parents, but such studies have been in the past limited to mouse and Drosophila sp.…”
mentioning
confidence: 99%
“…One approach used to study the genetics of phenotypic traits is to measure transcript expression in the hybrids relative to their parents, but such studies have been in the past limited to mouse and Drosophila sp. (Reiland and Norr 2002;Michalak and Noor 2003;Gibson et al 2004;Ranz et al 2004;Cui et al 2006;Hughes et al 2006;Rottscheidt and Harr 2007). Other studies have also focused on elucidating the genomic basis of heterosis of mollusc production (Hedgecock et al 2007) and plant production (Auger et al 2005;Swanson-Wagner et al 2006;Lippman and Zamir 2007;Ge et al 2008;Stupar et al 2008).…”
mentioning
confidence: 99%
See 1 more Smart Citation